If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -6x = -7(-2x + 8) + 6 Reorder the terms: -10 + -6x = -7(8 + -2x) + 6 -10 + -6x = (8 * -7 + -2x * -7) + 6 -10 + -6x = (-56 + 14x) + 6 Reorder the terms: -10 + -6x = -56 + 6 + 14x Combine like terms: -56 + 6 = -50 -10 + -6x = -50 + 14x Solving -10 + -6x = -50 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -10 + -6x + -14x = -50 + 14x + -14x Combine like terms: -6x + -14x = -20x -10 + -20x = -50 + 14x + -14x Combine like terms: 14x + -14x = 0 -10 + -20x = -50 + 0 -10 + -20x = -50 Add '10' to each side of the equation. -10 + 10 + -20x = -50 + 10 Combine like terms: -10 + 10 = 0 0 + -20x = -50 + 10 -20x = -50 + 10 Combine like terms: -50 + 10 = -40 -20x = -40 Divide each side by '-20'. x = 2 Simplifying x = 2
| 0.8x=148 | | -12x-5x=12-9x | | 7(6n+7)-7=-38+2n | | x^2-x^1-6=0 | | 5x^2-11x+12=0 | | 4(b+8)=17+7b | | -7p-39=-3(5p-3) | | 10(x+3)-(-9x-4)=n-5+3 | | -4(-k-2)=2k-34 | | 9+3-7-8+18-3= | | 6(-1-6x)=-6-6x | | X+2x^2=36 | | 1/6+x/9=x/12 | | 38+8n=-6(1+6n) | | 2x-2y+3x= | | 0.8x=128 | | y^2+361/4=-19y | | 12d^2-d-6=0 | | 3bx*x-2ax+3b=0 | | 3bx*x-2ax+3y=0 | | 3bx*x-2ax+by=0 | | x^6-1/27=0 | | 4n+7n= | | -8(x-8)+x=2(7-x) | | x(x-6)=x^2+4x+3 | | x(x-6)=x^2+6x+11 | | 5x^2-11x-4=0 | | 60(5/12) | | 60(4/5) | | 60(x/4) | | 12(2k+11)=12(2k-12) | | -7-(-1)/-8-(-3)=-6/(-5) |